Determinants of a successful suburban shopping center - Ng, Alex Zhi Qiang (2008)
This study examines the relative importance of retail space attributes such as anchor tenant, tenant mix, internal layout, external design and promotional activities in determining the success of a suburban shopping center. The study also tests the hypothesis that anchor tenant is the most important determinant of success in suburban shopping centers.